2004
DOI: 10.1023/b:ajcp.0000027002.93526.bb
|View full text |Cite
|
Sign up to set email alerts
|

Religious Activity and Risk Behavior Among African American Adolescents: Concurrent and Developmental Effects

Abstract: This study examines how religious activity is associated with risk behaviors, concurrently and developmentally among urban African American adolescents. Seven hundred and five African American youths were interviewed annually during high school. Retention rates for the study exceeded 90%. Frequency of religious activity, sexual intercourse, and alcohol, cigarette, and marijuana use were assessed at each wave. Growth curve analyses found negative concurrent associations between religious activity and each of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
103
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(112 citation statements)
references
References 42 publications
8
103
1
Order By: Relevance
“…In addition, external constraints (e.g., parental rules and monitoring) and individual constitutional factors (e.g., sensation seeking) are hypothesized to impact the socialization experiences . The protective factors selected for the present study are high parental monitoring (Peterson et al, 1994;Schulenberg and Maggs, 2002;Wood et al, 2004), low sensation seeking (Arnett, 2005;Bates et al, 1985;Jackson et al, 2005), involvement with nonsubstance-using peers (Bates and Labouvie, 1997;Jackson et al, 2005;Wood et al, 2004), high religiosity Steinman and Zimmerman, 2004;Wallace et al, 2003), high achievement in school (Newcomb et al, 2002), and strong bonding to school (Hawkins et al, 1992). All of these measures tap critical elements of the SDM.…”
Section: Potential High School Protective Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, external constraints (e.g., parental rules and monitoring) and individual constitutional factors (e.g., sensation seeking) are hypothesized to impact the socialization experiences . The protective factors selected for the present study are high parental monitoring (Peterson et al, 1994;Schulenberg and Maggs, 2002;Wood et al, 2004), low sensation seeking (Arnett, 2005;Bates et al, 1985;Jackson et al, 2005), involvement with nonsubstance-using peers (Bates and Labouvie, 1997;Jackson et al, 2005;Wood et al, 2004), high religiosity Steinman and Zimmerman, 2004;Wallace et al, 2003), high achievement in school (Newcomb et al, 2002), and strong bonding to school (Hawkins et al, 1992). All of these measures tap critical elements of the SDM.…”
Section: Potential High School Protective Factorsmentioning
confidence: 99%
“…Protective factors have been defined differently across studies (see Stouthamer-Loeber et al, 2002, for a detailed discussion). Some researchers have referred to variables as if they are either uniquely protective or uniquely related to risk (e.g., Rae-Grant et al, 1989).…”
Section: Potential High School Protective Factorsmentioning
confidence: 99%
“…Because many health problems experienced by African Americans are related to early health behaviors, it is important to examine factors related to positive health behavior patterns during late adolescence and early adulthood (Steinman & Zimmerman, 2004). For example, college represents a major developmental transition, which may be a time of personal growth as well as stress.…”
mentioning
confidence: 99%
“…For white Christians, religion and traditionalist sexual norms are often closely connected, and thus higher religious commitment is usually quite predictive of sexual behavior patterns (Patterson and Price, 2012;Regnerus, 2007;Wright, 2013;Wright et al, 2013;but see Perry, 2017a). Yet, even though black Americans tend to be more conventionally religious than whites on average (Shelton & Emerson, 2012), research has shown that black Americans, and especially black men, do not tend to connect their religious piety to their sexual norms and behaviors to the extent that whites do (Bearman & Bruckner, 2001;McCree et al 2003;Regnerus, 2007;Steinman & Zimmerman, 2004). These differential patterns of connecting religion and morality to sexual behavior largely stem from what religion has historically meant for different ethno-religious communities.…”
Section: Theorizing the Link Between Race Pornography Viewership Anmentioning
confidence: 99%